Indigenous Knowledge of Medicinal Plants and Attainment of SDG3: A Systematic Literature Review (Space and Culture, India, 2023)
Attainment of Sustainable Development Goals (SDGs) is a critical issue for the United Nations in the 21st Century. These 17 SDGs have specific targets to achieve these goals. To achieve a more sustainable future, 193 countries agreed to work on these 17 SDGs by 2030. Out of these 17 SDGs, this paper focuses on attaining SDG 3 through indigenous knowledge. The researchers explored previous studies by other researchers worldwide and global reports related to medical plants. They discussed the role of folk medicine in attaining the third goal of sustainable development (SDG3). Target 3.3 of SDG 3 focuses on eliminating combat hepatitis, waterborne diseases, Malaria, and other communicable diseases, and target 3.4 of SDG 3 focuses on reducing non-communicable diseases through prevention and treatment. Therefore, the focus of the study is to find out the specific plants which can be used for the treatment of various types of diseases through meta-analysis protocol and systematic reviews. Ninety articles are screened by keeping in view the set criteria. The study selected 50 scientific papers after excluding some papers due to the unavailability of full papers and duplicate copies of the articles. The researchers selected those papers whose citation is good. Previous researchers discussed that some plants and their parts—folk medicines— are often used to cure various communicable and non-communicable diseases like diabetes, cancer, Malaria, COVID-19, infections, pain, liver problems, etc., by certain groups and communities due to its lesser price, effortlessness, easy accessibility and affordability.